The The Merits of Online Learning Communication in Overcoming The Constraints of Communication Offline Education - Erna Dwinata (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This research highlights the weaknesses of communication patterns in offline learning which eventually become opportunities for online learning communication methods. The analysis in this study discusses the various advantages offered by online learning communication, revealing innovative methods and adaptive strategies that contribute to a more dynamic and effective way of delivering material experience. The method used in this study is the literature review method. Preparation of a literature review involves several stages, including finding relevant literature and evaluating literature sources. At the end of the findings will be presented 10 components that make online learning communication a tool to improve the practice of educational communication and overcome the challenges faced by conventional methods. Keywords: Online learning communication, offline learning communication, communication